The Harran Poet Yusuf b. Fazlullah es-Sekâkînî’s Life, Literary Personality, and Understanding of Zuht - Ahmet Aslan (Şarkiyat Mecmuası)
Zuht poetry is a literary art form that expresses the sublime meanings of human spirituality, and as such has always shown itself to be present in the history of Arabic literature. With the encouragement of the religion of Islam, its presence has increased even more, with ascetic poetry having become an important school of Islamic literature. This article deals with the life and ascetic poetry of Yusuf b. Fazlullah es-Sekâkînî, who lived in Harran and is one of the important poets of this school. Es-Sekâkînî was an ascetic, a scholar, and an important poet who wrote in the field of asceticism. The sources that have information about him mentioned how he wrote a lot of poetry in the field of asceticism and vera [an advanced level of taqwa/pious devotion] and showed him to be among the famous ascetic poets of his time. However, most of his poems havebeen lost to time, with only 12 couplets from a eulogy and an elegy having survived to the present day. For this reason, no scientific study has been done on him or his poetry. This study attempts to shed light on his poetry and understanding of asceticism based on his poems in the sources. The study provides a summary of the development process of the ascetic school in Arabic literature, as well as information about es-Sekâkînî’s life and the political and cultural environment in which he lived. His poems that have survived to the present and Turkish translations are also presented, as well as information about his literary personality and style. The study has attempted to reveal his thoughts on asceticism by analyzing his poems, with the conclusion providing inferences based on the study.